2016
DOI: 10.1002/aur.1658
|View full text |Cite
|
Sign up to set email alerts
|

Threatening faces fail to guide attention for adults with autistic‐like traits

Abstract: Individuals diagnosed with autistic spectrum conditions often show deficits in processing emotional faces relative to neurotypical peers. However, little is known about whether similar deficits exist in neurotypical individuals who show high-levels of autistic-like traits. To address this question, we compared performance on an attentional blink task in a large sample of adults who showed low- or high-levels of autistic-like traits on the Autism Spectrum Quotient. We found that threatening faces inserted as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 95 publications
4
27
0
Order By: Relevance
“…The faces were converted to grey scale, reduced in size (width 250 pixels & height 350 pixels), and edited to ensure all faces had similar lighting, head sizes, and eyes at the same level. T1 stimuli consisted of two generic dog faces (drawn from) 58 . The choice of these stimuli was based on the fact that they yielded a robust AB in previous studies 58,64 , as well as because they were visually distinct from both T2 and distractors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The faces were converted to grey scale, reduced in size (width 250 pixels & height 350 pixels), and edited to ensure all faces had similar lighting, head sizes, and eyes at the same level. T1 stimuli consisted of two generic dog faces (drawn from) 58 . The choice of these stimuli was based on the fact that they yielded a robust AB in previous studies 58,64 , as well as because they were visually distinct from both T2 and distractors.…”
Section: Methodsmentioning
confidence: 99%
“…T1 stimuli consisted of two generic dog faces (drawn from) 58 . The choice of these stimuli was based on the fact that they yielded a robust AB in previous studies 58,64 , as well as because they were visually distinct from both T2 and distractors. Distractor stimuli consisted of twelve KDEF faces that had scrambled facial features (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that the required sample size was 36 people. The high-and low-AQ groups were divided according to previous grouping criteria [31,32] and the range of AQ scores for the two groups [33,34]. According to their total scores, those who scored in the top 20% and bottom 20% were selected.…”
Section: Participantsmentioning
confidence: 99%